Design and Basic Evaluation of Virtual IPv4-based CYPHONIC adapter - Ren Goto; Taiki Yoshikawa; Hijiri Komura; Kazushige Matama; Chihiro Nishiwaki; Katsuhiro Naito (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The rapid spread of cloud services and the Internet of Things (IoT) leads to a request for secure communication between devices, called zero-trust security. However, security tends to be a low priority compared to the designated service because zero-trust security requires security knowledge. Therefore, a secure communication framework for developers' service development process is essential as the security measures. The authors have developed CYber PHysical Overlay Network over Internet Communication (CYPHONIC) for secure end-to-end communication between devices. Since the CYPHONIC provides secure communication, it also performs as the secure communication framework. The current implementation requires installing the device program into the end devices to join our overlay network. However, it should support general devices such as embedded devices or dedicated service servers even if they refuse to install the additional program. This paper proposes a new technology to support these general devices without installing the device program into the devices. We developed a CYPHONIC adapter to provide secure communication to general devices. It shows that general devices can communicate over the overlay network through the proposed CYPHONIC adapter.